The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5376/ija.2017.07.0013
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton Growth on Three Bio-substrates and Its Influence on the Performance of Jaraqui (<i>Semaprochilodus insignis</i>)

Abstract: Two experiments were conducted using plant substrates viz. bamboo (Bambusa vulgaris), ambay (Cecropia pachystachya) and leucaena (Leucaena leucocephala) without and with fish to evaluate their suitability for periphyton development, and influence on water quality and growth performance of jaraqui (Semaprochilodus insignis). In the first experiment of 45 days, carried out with only the substrates, periphyton growth and water quality were assessed, while in the second experiment of 120 days fish growth was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…The results from this study prove that even under low saline groundwater conditions, bamboo substrate has better periphyton growth compared to the other substrates used in this study. The periphyton quality assessment based on chlorophyll a observed in low saline groundwater was found to be on par with the chlorophyll a values observed from different studies in freshwater [19], and the higher values of chlorophyll a were reported in bamboo [28] (Table 2) as it was observed in the present study with higher periphyton growth in bamboo substrate compared to the other substrates. In contrast, Richard et al [8] have reported higher levels of dry matter and chlorophyll a on meshed substrates (mosquito net and garden net) than on smooth substrate (wood and plywood).…”
Section: Discussionsupporting
confidence: 82%
“…The results from this study prove that even under low saline groundwater conditions, bamboo substrate has better periphyton growth compared to the other substrates used in this study. The periphyton quality assessment based on chlorophyll a observed in low saline groundwater was found to be on par with the chlorophyll a values observed from different studies in freshwater [19], and the higher values of chlorophyll a were reported in bamboo [28] (Table 2) as it was observed in the present study with higher periphyton growth in bamboo substrate compared to the other substrates. In contrast, Richard et al [8] have reported higher levels of dry matter and chlorophyll a on meshed substrates (mosquito net and garden net) than on smooth substrate (wood and plywood).…”
Section: Discussionsupporting
confidence: 82%
“…The substrates (rice straw and kanchi) added to the pond significantly increases fish production and did not negatively affect water quality; therefore, the treatments with substrates were better than the treatment without a substrate (control). Keshavanath et al (2017) conducted two experiments using plant substrates viz. bamboo, Bombay and Leucaena without and with fish to evaluate their suitability for periphyton development, and their influence on water quality and growth performance of Karachi (Semaprochilodus insignis).…”
Section: Discussionmentioning
confidence: 99%
“…Fish/prawn culture is enhanced by fertilization, substrate introduction or biofuels technology. (Keshavanath et al 2017) Periphyton production in ponds is enhanced through the provision of substrate, such as bamboo poles. Wahab et al (1999) reported that yields of calabash, Labeo calabash (Hamilton),were 80% higher in ponds using bamboo substrates as compared to the control ponds without substrate.…”
Section: Introductionmentioning
confidence: 99%